The Techniques of Football Dribbling in Learning Physical Education, Sports, and Health - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research is a type of descriptive research. This study aims to determine the level of football dribbling techniques in physical education, sports, and health learning. The population is all grade IV, V, and VI students of SD Negeri Mamajang 2. Researchers selected samples using random samples (Probability Sampling), the selected sample was 15 students of grade VI A. The data analysis technique used was descriptive statistical analysis. Football dribbling techniques in physical education learning sports and health are in the category of less once by 0% (0 students), the category of less, by 13.33% (2 students). The medium category is 20% (3 students), the good category is 6.7% (1 student) and the very good is 60% (9 students). Based on an average score of 24.92. Football dribbling techniques in physical education, sports, and health learning are included in the very good category.